From Behaviorism to Cognitive Neuroscience: An 83-Year Bibliometric Analysis of Mental Arithmetic Research in Educational Psychology (1942–2024) - Leiden Levita Sahensolar; Isma Widiaty; Mubiar Agustin (Jurnal Pendidikan MIPA, 2026)
This study addressed the absence of a comprehensive bibliometric analysis of mental arithmetic research in educational psychology by systematically mapping its evolutionary trajectory over 83 years (1942–2024). Using Scopus database searches, 1,749 unique deduplicated records were retrieved, with 626 "arithmetic skills" records serving as the core dataset for descriptive bibliometric analyses of temporal trends, publication characteristics, and theoretical implications. Results revealed exponential growth in publications across five research eras, with the Digital Era (2010–2019) and Contemporary Era (2020–2024) collectively contributing 72.2% of the total output. Journal articles dominated the corpus (85.1%); English-language publications accounted for 93.9% of the dataset; and the low proportion of review articles (4.2%) indicates that knowledge synthesis remains underdeveloped relative to empirical output. Bibliometric patterns reveal a progressive paradigm shift from behaviorist frameworks to cognitive modeling, and then to cognitive-neuroscientific approaches, accelerated by advances in neuroimaging and educational technology. This study provides the first systematic 83-year bibliometric mapping of mental arithmetic research, offering an evidence base to guide future research directions, identify conceptual gaps, and inform mathematics education curriculum and policy, particularly relevant for contexts such as Indonesia, where arithmetic achievement gaps persist. Keywords: bibliometrics, mental arithmetic, educational psychology, mathematical cognition.